The Mediating Role of Workplace Friendship in the Effect of Workplace Loneliness on Organizational Identification (Third Sector Social Economic Review, 2026)
The aim of this study is to determine the levels of workplace loneliness, organizational identification, and workplace friendship among rolling mill workers in Karabük, and to identify the relationships between these concepts. Data was collected from 419 employees of rolling mills that are members of the Karabük Private Sector Iron and Steel Rolling Mills Association using convenience sampling method. Analysis of the data by using SPSS 22 revealed that employees experienced partial workplace loneliness, but their levels of organizational identification and workplace friendship were positive at an acceptable level. Workplace loneliness, organizational identification, and workplace friendship levels were also compared in terms of employees' demographic characteristics. The comparisons revealed no significant differences in terms of gender, age, and income. When the data was analyzed in terms of seniority, it was determined that although they were in different groups, lower-senior employees had more behaviors related to social friendship, workplace friendships, and valuing friendship compared to higher-senior employees. In terms of education level, primary school graduates formed more social friendships than university graduates and valued friendships more than high school/university graduates. Furthermore, workplace loneliness was found to negatively impact employees' organizational identification and workplace camaraderie. Conversely, workplace friendships were found to positively contribute to organizational identification. The mediation test results revealed that workplace friendships play a partial mediating role in the effect of workplace loneliness on the level of organizational identification.
Keywords: Workplace Loneliness; Organizational Identification; Workplace Friendship; Iron and Steel Industry; Rolling Mill